Bias Crime and Victimization Among Latinx Adults: Formal and Informal Help Seeking. Issue 23 (December 2022) - Lockwood, Sarah; Farrell, Amy; Cuevas, Carlos A.; Robles, Jesenia
Latinx adults have become increasingly vulnerable to bias motivated victimization. The impact of such incidents on Latinx communities is severely understudied, particularly concerning whether or not victims will seek help as a result of such events. Evidence within other victimization contexts demonstrate Latinx populations may be less likely to seek formal help from police, medical providers, and other formal authorities, relying instead on informal support networks such as family and friends. The current study sought to understand formal and informal help-seeking behavior among Latinx adults who experienced bias motivated victimization. The Understanding and Measuring Bias Victimization against Latinos study obtained rates of bias victimization and subsequent help-seeking behavior among Latinx adults who reported experiencing bias victimization (n = 315, 34.6% of full sample of 910). Those who experience bias victimization seek formal help at much lower rates than informal forms of support. Logistic regression analyses controlling the type of victimization demonstrated that participants who experienced a victimization constituting a hate crime were more likely to seek formal help compared to experiencing non-criminal bias events. Implications include addressing barriers to Latinx bias victims seeking forms of help, in addition to understanding the potential polyvictimization histories that predict why Latinx adults may decide to seek help.